Analisis Teks Sejarah dan Geografi untuk Meningkatkan Kemampuan Bahasa Arab Santri Zainul Hasan Genggong Probolinggo - Serli Rosida; Ainur Rofiq Sofa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of using history and geography texts as learning media in improving students’ Arabic language skills at Zainul Hasan Islamic Boarding School in Genggong Probolinggo. The background of this research departs from the need to present Arabic language learning that is more contextual and integrative, given the dominance of traditional methods that emphasize grammatical aspects alone. A descriptive qualitative approach was used with a case study method, involving classroom observation, in-depth interviews, and documentation as data collection techniques. The results showed that the integration of history and geography texts significantly improved students’ vocabulary acquisition, cultural understanding, as well as their reading, writing, and critical thinking skills. The obstacles faced include limited thematic teaching materials, lack of teacher training in content-based approaches, and the complexity of text language. The solutions offered include the development of thematic teaching modules, teacher training, the use of visual media, and collaborative learning strategies. This study concludes that the use of history and geography texts is not only effective in language acquisition, but also in building cross-disciplinary connections that support the holistic development of santri competencies.